Aplicación de la Metodología de Sistemas Blandos de Peter Checkland en la Prevención de la Infección del Virus del Papiloma Humano en los Alumnos de Primer Año de Media del C.E N° 0031 María Ulises Dávila Pinedo – Morales - Portocarrero Gutiérrez, Cristian Edgardo (2015)
This research was conducted with the students of the first year of secondary Education Center 0031, which corresponds to Backpacks district, province and department of San Martin. The problem, hypothesis and general objective have been formulated according to the variables: independent, Soft Systems Methodology Checkland Peter; and dependent Infection Prevention Human Papillomavirus. The theoretical demonstration on the Application of Soft Systems Methodology of Checkland Peter, to achieve educational objectives and likewise the more sophisticated prevention of infection of human papillomavirus, has been applied in a heavily armed cultural and social context of the School 0031. Two hypotheses were formulated: the alternative hypothesis, which holds that the application of the Soft Systems Methodology Peter Checkland, improve the prevention of infection Human Papillomavirus in the freshmen of the EC No. 0031 MARIA DAVILA PINEDO ULYSSES - MORALES, while the null hypothesis that supports the absence of significant relevance. The study has a quasi-experimental design, a sample of 40 students was formed two groups: experimental and control both the first and the second consists of 20 students aged relative whose variables such as sex, etc. They will be controlled; The procedure consisted of applying a pre test and post test for both the control group as for the experimental. The hypothesis testing was conducted, the results showed a significant relevance when doing The Application of Soft Systems Methodology of Checkland Peter. Consequently the findings set its generality, pointing out that the experimental group significantly improved future prevention of contracting the Human Papillomavirus (HPV), unlike the control group was not significant